Monosodium glutamate in standard and high-fiber diets: Metabolic syndrome and oxidative stress in rats - Diniz, Yeda Sant'; Faine, Luciane A.; Galhardi, Cristiano M.; Rodrigues, Hosana G.; Ebaid, Geovana X.; Burneiko, Regina C.; Cicogna, Antonio C.; Novelli, Ethel L. B. (Elsevier, 2005)
Objective: This study determined the effects of adding monosodium glutamate (MSG) to a standard diet and a fiber-enriched diet on glucose metabolism, lipid profile, and oxidative stress in rats. Methods: Male Wistar rats (65 ± 5 g, n = 8) were fed a standard diet (control), a standard diet supplemented with 100 g of MSG per kilogram of rat body weight, a diet rich in fiber, or a diet rich in fiber supplemented with 100 g of MSG per kilogram of body weight. After 45 d of treatment, sera were analyzed for concentrations of insulin, leptin, glucose, triacylglycerol, lipid hydroperoxide, and total antioxidant substances. A homeostasis model assessment index was estimated to characterize insulin resistance. Results: Voluntary food intake was higher and feed efficiency was lower in animals fed the standard diet supplemented with MSG than in those fed the control, fiber-enriched, or fiber- and MSG-enriched diet. The MSG group had metabolic dysfunction characterized by increased levels of glucose, triacylglycerol, insulin, leptin, and homeostasis model assessment index. The adverse effects of MSG were related to an imbalance between the oxidant and antioxidant systems. The MSG group had increased levels of lipid hydroperoxide and decreased levels of total antioxidant substances. Levels of triacylglycerol and lipid hydroperoxide were decreased in rats fed the fiber-enriched and fiber- and MSG-enriched diets, whereas levels of total antioxidant substances were increased in these animals. Conclusions: MSG added to a standard diet increased food intake. Overfeeding induced metabolic disorders associated with oxidative stress in the absence of obesity. The fiber-enriched diet prevented changes in glucose, insulin, leptin, and triacylglycerol levels that were seen in the MSG group. Because the deleterious effects of MSG, i.e., induced overfeeding, were not seen in the animals fed the fiber-enriched diets, it can be concluded that fiber supplementation is beneficial by discouraging overfeeding and improving oxidative stress that is induced by an MSG diet. © 2005 Elsevier Inc. All rights reserved.
Keywords: Diets; Fiber; Metabolic parameters; Monosodium glutamate; Oxidative stress; Rats; antioxidant; glucose; glutamate sodium; insulin; leptin; lipid hydroperoxide; triacylglycerol; animal experiment; blood analysis; body weight; controlled study; diet supplementation; food intake; glucose blood level; glucose metabolism; high fiber diet; insulin blood level; insulin resistance; lipid analysis; male; metabolic syndrome X; nonhuman; oxidative stress; priority journal; protein blood level; rat; triacylglycerol blood level; Animals; Blood Glucose; Dietary Fiber; Energy Intake; Food Additives; Insulin; Leptin; Lipid Metabolism; Male; Metabolic Syndrome X; Oxidative Stress; Random Allocation; Rats, Wistar; Sodium Glutamate; Triglycerides; Animalia; Rattus norvegicus